Prevention of social exclusion and role of antenatal care by BRAC community health workers in improving safe motherhood and neonatal care in urban slums of Bangladesh - Jolly, Saira Parveen; Chowdhury, Tridib Roy; Rahman, Mahfuzar; Alam, Ariful; Afsana, Kaosar (PLOS ONE, 2022)
This article was published in The Plos One [ © 2020 Jolly et al. This is an open access article distributed under the terms of the Creative Commons Attribution License] and the definite version is available at: https://doi.org/10.1371/journal.pone.0235340 The Journal's website is at: https://journals.plos.org/plosone/article?id=10.1371/journal.pone.0235340